Pergeseran Bahasa Baku: Ragam Bahasa Elitis dalam Akun Instagram Humor Recehku - Wiwik Ariesta; Atika Lisamawati Nur Qoyyimah; Markhamah Markhamah (Universitas Mulawarman, 2021)
The purpose of this study is to describe elitist language on the Humor Recehku Instagram account, namely (1) non-standard word forms; (2) abbreviated forms that cause non-standard; and (3) word forms from foreign languages. The method used in this research is the descriptive method. The data collection technique was done by observing and taking notes. Data analysis used Miles and Huberman qualitative analysis, namely data reduction, data presentation and drawing conclusions and levers. This research leads to the content analysis “content analysis”. The data in this study are in the form of words, phrases, and sentences that experience language shifts in an elitist form. The results of this study indicate that there is a language shift in the case of using elitist language in the Humor Recehku Instagram account. First, non-standard word forms include non-standard words without a play (emang, gini, telfon, sampe, ngerasa dan sebagainya); non-standard words with a pun (Oktrouble dan gw); and non-standard words weakening phonemes (males, denger, bener-bener, ye, cakep, anjeng, kecapean, dan temen). Second, abbreviations that cause non-standard abbreviated standard words (sm, org, krn, dan trs); and abbreviated non-standard words (not and yesterday2). Third, foreign language words are divided into (typing, excuse, mood and so on); phrase (self-reminder, close friend IG); and sentences (is the best kind of sleep, oh well honey, you keep your small circle, and friend with many but trust any).